Rewiring Meiosis for Crop Improvement - Kuo, Pallas; Da Ines, Olivier; Lambing, Christophe (Frontiers in Plant Science, 2021)
Meiosis is a specialized cell division that contributes to halve the genome content and reshuffle allelic combinations between generations in sexually reproducing eukaryotes. During meiosis, a large number of programmed DNA double-strand breaks (DSBs) are formed throughout the genome. Repair of meiotic DSBs facilitates the pairing of homologs and forms crossovers which are the reciprocal exchange of genetic information between chromosomes. Meiotic recombination also influences centromere organisation and is essential for proper chromosome segregation. Accordingly, meiotic recombination drives genome evolution and is a powerful tool for breeders to create new varieties important to food security. Modifying meiotic recombination has the potential to accelerate plant breeding but it can also have detrimental effects on plant performance by breaking beneficial genetic linkages. Therefore, it is essential to gain a better understanding of these processes in order to develop novel strategies to facilitate plant breeding. Recent progress in targeted recombination technologies, chromosome engineering, and an increasing knowledge in the control of meiotic chromosome segregation have significantly increased our ability to manipulate meiosis. In this review, we summarize the latest findings and technologies on meiosis in plants. We also highlight recent attempts and future directions to manipulate crossover events and control the meiotic division process in a breeding perspective.